2020
DOI: 10.21203/rs.3.rs-122199/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Topical Application of Human Breast Milk, Chlorhexidine and Dry Cord Care on Neonatal Umbilical Cord Separation Time and Rate of Cord Infection : Cluster Randomized Trial

Abstract: Background- Annually 1 million newborns worldwide die of infection caused by bacteria that enter the body via the umbilical cord. Regarding this the Ethiopia national strategy of new born and child survival identified Chlorhexidine as one of the high impact interventions to minimize neonatal mortality. Whereas, studies have shown Human breast milk application to the neonatal umbilical cord has a shorter cord separation time and lower rate of infection than Chlorhexidine or dry cord care. Method- From May to No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…9 It is one of the most affordable and efficacious interventions in preventing infections and in improving neonatal survival in low-resource settings such as ours. So far, studies have shown chlorhexidine application has a lower infection among neonatal intensive care units, 10 when WHO recommends keeping the cord clean and not to apply anything to it (dry cord care). 11, 12 Though there are studies regarding the application of CHX for umbilical cord care but not in Indian population and also culture of the microorganisms are not done till date to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…9 It is one of the most affordable and efficacious interventions in preventing infections and in improving neonatal survival in low-resource settings such as ours. So far, studies have shown chlorhexidine application has a lower infection among neonatal intensive care units, 10 when WHO recommends keeping the cord clean and not to apply anything to it (dry cord care). 11, 12 Though there are studies regarding the application of CHX for umbilical cord care but not in Indian population and also culture of the microorganisms are not done till date to our knowledge.…”
Section: Introductionmentioning
confidence: 99%